Adherence to Preoperative Cardiac Clearance Guidelines in Hip Fracture Patients. Issue 11 (November 2015) - Stitgen, Andrea; Poludnianyk, Kim; Dulaney-Cripe, Elizabeth; Markert, Ronald; Prayson, Michael
Abstract : Objectives: To identify if preoperative cardiac consultations are made in accordance with the American College of Cardiology (ACC) Foundation and American Heart Association (AHA) guidelines and the delays in care after unnecessary consults. Design: Retrospective review. Setting: Level 1 trauma center. Patients/Participants: A retrospective review of 315 patients with hip fractures admitted over a 2-year period was conducted. After excluding patients younger than 65 years and those admitted by the general surgery trauma service, 266 patients were included. Intervention: Criteria meeting the ACC/AHA guidelines for preoperative cardiac consultations. Main Outcome Measurements: Time to surgical intervention and total hospital length of stay. Results: Of the 266 patients reviewed, 55 patients (21%) received preoperative cardiac consultations, whereas 211 patients did not. Only 16 of the 55 patients (29%) with cardiac consults met the ACC/AHA guidelines, whereas 39 patients received unnecessary cardiac consults. Of the 247 patients (39 with consults and 208 without consults) who did not meet the guidelines, those who received a preoperative cardiac consult had a significantly longer average time to surgery (43.9 vs. 23.1 hours) ( P = 0.005) and hospital length of stay (7.9 vs. 5.3 days) ( P = 0.010). There were no significant differences in postoperative complications or disposition. Conclusions: Preoperative cardiac consults are frequently overused and lead to delays to surgical intervention and longer hospital length of stay while not revealing any further need for cardiac intervention or changing the rate of adverse events. Stricter adherence to the ACC/AHA guidelines will help decrease surgical delay and hospital length of stay. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.